Consumer society critical issues and environmental consequences - Smart, Barry; SAGE Knowledge (Online service). (Los Angeles, Calif. Sage, 2010)
"Has consumer culture got out of hand? Are the costs of universal access and pollution too great to bear?This comprehensive, lively and informative book will quickly be recognized as a benchmark in the field. It brings together a huge set of resources for thinking about consumer culture and examining its origins and consequences within a global context. Adept in handling a complex range of theories, Consumer Society scrupulously uses examples throughout to inform and enhance understanding. Smart writes with verve and feeling and has produced a book that simultaneously covers and enlarges our understanding of consumer culture. Clear, engaging and original, this book will be important reading for all those interested in our global culture of consumption including students of sociology, social geography and cultural studies."-Provided by publisher.
Consuming: Historical and Conceptual Issues -- Consumer Choice: Rhetoric and Reality -- Cultivating Consumers: Advertising, Marketing, and Branding -- Designing Obsolescence, Promoting Consumer Demand -- Globalization and Modern Consumer Culture -- Consequences of Consumerism -- An Unsustainable All-Consuming World -- Consuming Futures I: Business as Usual -- Consuming Futures II: 'Green' and Sustainable Alternatives.
Includes bibliographical references (p. [226]-252) and index.
Also available in print version.
Keywords: Consumption (Economics) -- Social aspects